Get up and get moving—early mobilisation after hip fracture surgery - Sallehuddin, Hakimah; Ong, Terence (Oxford University Press, 2020)
Early mobilisation must follow on from early hip fracture surgery as delayed ambulation leads to poor post-operative outcomes. Early mobilisation post-operatively was associated with better mobility and more discharges from hospital. Embedding it into routine clinical practice will require involvement of the orthogeriatric multidisciplinary team.